Prosesi Adat Sebelum Perkawinan Suku Rejang Di Kabupaten Rejang Lebong Dalam Perspektif Hadits - Syah, Mabrur; Supian, Aan (Berasan: Journal of Islamic Civil Law, 2023)
The study aims to determine the traditional procession before the marriage of the Rejang tribe in  Rejang Lebong Regency in the perspective of hadith. The method used in this study  is qualitative research with library data sources using qualitative descriptive analysis techniques. The results of this study, first, the traditional procession before the marriage of the Rejang tribe began from mediak, bekulo, betunang, and sembeak sujud, majok sematen / bakea mengenyan, and deliberation in determining the place of residence after manikah and determining the status of congenital property.  The two traditional processions before the marriage of the Rejang tribe when viewed in the perspective of hadith t are in line with Islamic teachings, such as mediac  customs, namely the introduction of bachelors and girls to the Rejang tribe, such as ta'aruf whose implementation must pay attention to ethical norms in Islamic associations, bekulo and betunang customs are  identical to khitbah activities, the custom of prostration There is an element of learning ethics and manners in communicating for brides-to-be in everyday life  and the custom of determining the place of residence after manikah and determining the status of property is carried out by deliberation. The interaction of Islam with the Rejang culture at the ceremony before the wedding and the tools used in the ceremony have been acculturation, accomodation and integration. As the beginning of the activity begins  with the recitation of the basmalah and the ceremony ends with the recitation of the congratulatory prayer.